Perusahaan Dengan Keputusan Pendanaan Sebagai Variabel Moderating Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia - Baihaqi Ammy (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The sample used was 9 companies. To obtain the data needed in this research, the authors use documentation techniques from data published by the company on the IDX's official website www.idx.co.id. As well as financial statements owned by the company. The data analysis technique in this research is using classical assumption test, simple linear regression, t test, F test, coefficient of determination and moderating regression analysis. Data processing in this study used the SPSS (Statistics Package for the Social Sciences) software program version 26.00 for windows. Based on the results of the study, it can be concluded that the size of the company has no effect on the value of the company in the pharmaceutical company on the IDX. Profitability has no effect on firm value in pharmaceutical companies on the IDX. The funding decision as a moderating variable is not able to moderate the relationship between firm size and firm value in pharmaceutical companies on the IDX. The funding decision as a moderating variable is not able to moderate the relationship between profitability and firm value in Pharmaceutical Companies Listed on the Indonesian Stock Exchange Listed on the Indonesia Stock Exchange.